Correlation between Uterine Hemodynamics, Sex Steroid Hormone Concentrations, and Enzymatic Antioxidant Levels in Postpartum Buffaloes - Abdelnaby, Elshymaa A.; El-Shahat, Khaled; Abd-Allah, Saber; El-Sherbiny, Hossam R. (Journal of Buffalo Science, 2022)
The present investigation aimed to evaluate uterine hemodynamics in six multiparous postpartum buffaloes and their relationship with sex steroid hormone concentrations and enzymatic antioxidant levels. The buffaloes were examined by transrectal Doppler ultrasonography to record the vascular perfusion in uterine arteries of both ipsilateral and contralateral ones. All Doppler indices such as peak (PV) endpoints (EV) of velocity, peak systolic velocity (PSV), blood flow volume (BFV), resistance (RI), and pulsatility index (PI) were recorded from 1st to 6th postpartum. The blood samples were collected starting from 1st-week post-calving and every week thereafter following each ultrasound Doppler examination for assay of steroid hormones (progesterone and estradiol) and antioxidant (superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase, CAT) were measured. PV of the ipsilateral previously gravid arteries showed a linear pattern of significant (P=0.001) decline from the 1st week after parturition till the 6th week. This decline was also associated with a linear decrease in EV from the 1st week till the 6th week after birth. While contralateral PV and EV are not significantly changed throughout weeks after parturition. The levels of SOD and CAT are significantly elevated at 1st week postpartum compared to the 6th week after parturition. In contrast, the GPx levels did not reveal any significant differences during the puerperal period. Estradiol and progesterone declined from 1st to 5th week after parturition. PV of the ipsilateral uterine artery had a significant (P≤0.05) positive correlation with BFV (r=0.49), estradiol 17- α(r=0.98) and progesterone (r=0.85). The same parameter showed a statically (P≤ 0.001) positive correlation with SOD (r=0.87) and CAT (r=0.92). While, Ipsilateral uterine RI showed a significant (P≤0.05) negative correlation with PV(r=-0.85), BFR ((r=-0.62), estradiol 17- α(r=-0.52), and progesterone (r=-0.88), in addition, RI also correlated negatively with both SOD (r=-0.57) and CAT (r=-0.63). Progesterone and estrogen levels are strongly correlated with SOD and CAT. The uterine hemodynamics in buffaloes is affected by the day of the postpartum period. SOD and CAT antioxidants recorded herein, except GPx, increase in the 1st weeks of calving and are affected by the day of the postpartum period.